Euthanasia of whales: the effect of .375 and .485 calibre roundnosed, full metal-jacketed rifle bullets on the central nervous system of the common minke whale - Oen, E. O.; Knudsen, S. K. (J. Cetacean Res. Manage., 2023)
The effect of rifle projectiles used for the euthanasia of stranded or hunted whales has been an issue for debate, in particular in the International Whaling Commission (IWC) and the North Atlantic Marine Mammal Commission (NAMMCO). In the Norwegian hunt for common minke whales, 9.3mm, .375 or .458 calibre rifles are used as backup weapons to euthanise whales that are not deemed dead after being hit with a harpoon grenade. When using the rifle, the hunters aim at the brain of the animal. The present study investigates the effects of the two rifle calibres .375 and .458 and round nosed, full-metal jacketed bullets in 29 common minke whales. The whales were examined post mortem shipboard and 22 of the brains were fixed in situ and later subjected to gross and light microscopic examination. The results show that the two types of bullets are fully capable of penetrating the skull and spinal bones of common minke whales and fatally damaging the central nervous system, resulting in immediate or very rapid loss of consciousness.